COVID-19 in Children: A Narrative Review - Razavi, Alireza; Davoodi, Lotfollah; Shojaei, Layla; Jafarpour, Hamed (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: In December 2019, coronavirus (CoV) disease 2019 (COVID-19) was detected in Wuhan, China, which is known as severe acute respiratory syndrome CoV 2 (Severe acute respiratory syndrome [SARS]-CoV-2). AIM: This study attempted a narrative review of the researches about COVID-19 in children. METHODS: We searched all articles between 2000 and April 2020 in PubMed, Scopus, and ScienceDirect related to COVID-19 in children, using the following terms: “COVID-19,” “coronavirus,” “SARS-CoV-2” in combination with “pediatrics,” or “children.” RESULTS: The most common method of transmitting the disease to children was through close contact with family members through respiratory droplets. Coinfection is common in pediatric with COVID-19 infection. One of the most important transmission routes is oral feces. The severity of the disease was mild or asymptomatic in most children. The most common clinical symptoms were fever and cough, and gastrointestinal symptoms were more common in children than in adults. Infants and preschoolers had more severe clinical symptoms than older children. The most common radiographic findings from the lungs were bilateral ground-glass opacity. Increased procalcitonin and lactate dehydrogenase should be considered in children. The use of intravenous immunoglobulin, lopinavir/ritonavir, and oseltamivir, along with oxygen therapy, had the greatest effect on improving children’s conditions. CONCLUSIONS: The most important way to prevent this disease in children is to follow the health tips of family members. Although the number of children with the disease is low, children are vulnerable to infection. Antiviral medications along with the use of muscle relaxants and oxygen therapy have a great impact on children’s condition.